Optical, electric, and magnetic properties of molecules : a review of the work of A.D. Buckingham - Buckingham, A. D. (Amyand David) (Elsevier, 1997)
This book celebrates the career and scientific accomplishments of Professor David Buckingham, who is due to retire from his Chair at Cambridge University in 1997. The adopted format comprises reprints of a number of David Buckingham's key scientific papers, each one or two of these preceded by a review of the corresponding area of David's wide-ranging research interest. Each reviewer is recognised as an expert in that field of interest and has some close association with David Buckingham, as a scientific colleague and/or a former research student. The book should serve as a distinctive reference source, both retrospective and prospective, for the field of chemical physics with which the name A.D. Buckingham is associated. The editors opted to reprint a majority of early classic Buckingham papers, balanced by some of David Buckingham's more recent publications. Reprinted papers have been placed into a general scientific context that covers prior influences on, and later impacts by, the work nominated for review.